2022
DOI: 10.21776/ub.gramaswara.2022.002.02.02
|View full text |Cite
|
Sign up to set email alerts
|

Penguatan Kompetensi Guru Dalam Penyusunan Media Visual Digital Di Desa Toyomarto Kecamatan Singosari Kabupaten Malang

Abstract: Desa Toyomarto mempunyai fasilitas pendidikan terdiri dari tingkat SD sampai dengan SMU yakni ada 5 bangunan SD/MI (SDN Toyomarto I, SDN Toyomarto II, SDN Toyomarto III, SDN Toyomarto IV, dan MI Al-Ma’arif 06), 1 bangunan SMP (SMP Islam Al-Ma’arif 02) dan 1 bangunan SMK (SMK Insan Mandiri). Upaya meningkatkan kualitas di bidang pendidikan dan untuk mendorong peningkatan kompetensi guru yang memiliki kecerdasan dan daya saing yang lebih baik, maka arah kegiatan yang ditempuh adalah meningkatkan kualitas proses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Previous research in elementary schools showed that there were differences in teacher competency in villages and cities, such as research by Vito [15], Saripudin [16], Hamidi [17], and Hardinata [18]. Other studies, such as Ulfatin's, found no significant differences in teacher competence between cities and villages [19] and Purnama [20].…”
Section: Introductionmentioning
confidence: 97%
“…Previous research in elementary schools showed that there were differences in teacher competency in villages and cities, such as research by Vito [15], Saripudin [16], Hamidi [17], and Hardinata [18]. Other studies, such as Ulfatin's, found no significant differences in teacher competence between cities and villages [19] and Purnama [20].…”
Section: Introductionmentioning
confidence: 97%